Soil enzymes activity: Effect of climate smart agriculture on rhizosphere and bulk soil under cereal based systems of north-west India - Jat, Hanuman Sahay; Datta, Ashim; Choudhary, Madhu; Sharma, Parbodh Chander; Dixit, Bharti; Jat, Mangi Lal (Elsevier, 2021)
In agriculture production system, soil enzymes are important indicators of soil quality. Measurements of soil quality parameter changes are essential for assessing the impact of soil and crop management practices. Keeping this in view, an experiment was conducted to evaluate the enzyme activities namely dehydrogenase (DHA), β-glucosidase, acid and alkaline phosphatase (AcP & AlP), fluorescein diacetate hydrolases (FDH), cellulase, urease and aryl sulphatase in rhizosphere and bulk soil after 8 years of different management regimes. Soil organic carbon (SOC), moisture content and few enzyme indices such as enzymatic pH indicator (AcP/AlP), alteration index three (Al3) and geometric mean (GMea) were also measured. The treatments were conventional rice-wheat system (termed as scenario (Sc1), CT system), partial conservation agriculture (CA)-based rice-wheat-mungbean system (Sc2, PCA-RW), partial climate smart agriculture (CSA)-based rice-wheat-mungbean system (Sc3), partial CSA-based maize-wheat-mungbean system (Sc4), full CSA-based rice-wheat-mungbean system (Sc5), and full CSA-based maize-wheat-mungbean system (Sc6). Soil samples were collected from rhizosphere and away from roots (bulk soil) at 0-15 cm soil depth before sowing (from rhizosphere of previous crops), at maximum tillering, flowering, and after harvesting of wheat crop. Results showed that DHA activity was higher before sowing (59.8%), at maximum tillering (48.4%), flowering (8.6%) and after harvesting (19.1%) in rice based CSA systems (mean of Sc3 and Sc5) over maize based CSA systems (mean of Sc4 and Sc6) in rhizospheric soil. On average, β-glucosidase activity was significantly higher in rhizospheric soils of rice based system over maize based CSA system. Before sowing of wheat, significantly higher (21.4%) acid phosphatase activity was observed in rhizosphere over bulk soils of maize based CSA system. Significantly higher alkaline phosphatase activity was observed before sowing of wheat in bulk soils of rice (25.3%) and maize (38.5%) based CSA systems over rhizospheric soils. Rice based CSA systems showed 27% higher FDH activity than maize based systems. Significant interaction effect was observed between the managements and enzymes. SOC played an important role in regulating the enzymes activity both in rhizosphere and bulk soil. Significant variation in AcP/AlP, Al3 and GMea was observed among the managements. Therefore, CSA managements are beneficial in improving enzyme activities not only in rhizosphere but also in bulk soil where residues are retained thereby may help in improving nutrient cycling.